KONTRIBUSI IBU RUMAH TANGGA YANG BEKERJA TERHADAP KESEJAHTERAAN KELUARGA DI DESA KEMANTAN KECAMATAN AIR HANGAT TIMUR KABUPATEN KERINCI - sely mutia rantika; Ernawati Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to determine: 1) Obtain data about analyzing and discussing data about the contribution of working housewives to family income 2) Knowing the contribution of working housewives to the availability of clothing at home 3) Knowing the extent of the contribution of working housewives on the availability of household food. 4) Knowing the contribution of working housewives to the availability of household boards 5) Knowing the educational background of working housewives 6) Knowing the extent of the health condition of the working housewives' families. The population in this study were 1181 people, and the sample was taken by 5% of the population, namely 60 samples. This type of research is classified as quantitative descriptive. Because this research is essentially attempted to describe the research variables as described in the problem formulation. The results of this study indicate the following: 1) The contribution of working housewives to family welfare is for the contribution of 20 – 30% as many as 10 respondents (16.6%), while for the contribution of 31 – 40% as many as 33 respondents (55%) , and for the contribution <40% as many as 17 respondents (28.3%). So it can be concluded that the average contribution of the majority of housewives is in the 31-40% category as many as respondents (55%). The income condition of housewives in Kemantan Village, Air Hangat Timur District, Kerinci Regency mostly ranges between Rp. 500,000 – Rp 800,000/month, which is 34 people. 2) The condition of meeting the family needs of housewives who work in the village of Kemantan, Air Hangat Timur District, Kerinci Regency in meeting the needs of clothing (clothing) has an average score of 3 which is in the medium category 3) Conditions for fulfilling the needs of the family of housewives who work in Kemantan Village, Air Hangat Timur District, Kerinci Regency in meeting food needs (food) has an average score of 2.9 which is in the medium category, 4) Conditions for fulfilling the ability of the family of housewives who work in Kemantan Tinggi Village, Air Hangat Timur District Kerinci Regency in meeting the housing needs has an average score of 2.8 which is in the medium category. 5) The condition of the family of housewives who work in Kemantan Village, Air Hangat Timur District, Kerinci Regency in meeting educational needs has an average score of 2.9 which is in the medium category, with the highest frequency being 56.3% which is classified as in the moderately capable category. 6) The condition of the ability of housewives' families who work in Kemantan Village, Air Hangat Timur District, Kerinci Regency in meeting health needs has an average score of 2.7 which is in the medium category, with the highest frequency being 53.3% belonging to in the moderately capable category. Keywords: working housewife, family welfare